Ii. Bishop Wren and the Suppression of the Norwich Lecturers - King, Peter (The historical journal, 1968)
One of the most serious problems facing Archbishop Laud was the rapid growth of the Lecturer Movement during the 1620s and 1630s. The increasing numbers of graduates available, and the increasing amount of money donated to support them meant that the weekly lectures had become one of the chief “religious … organizations of the opposition”, and were beginning to “undermine the hierarchical principle”. The gravity of the situation was marked by the increasingly stringent regulation of the lecturers. They had originally been allowed to preach with very little control, but from the Canons of 1604 onwards they were made the subject of several new regulations. These culminated in the Directions of March 16296 which, although issued by Archbishop Abbot, were based upon suggestions made by Laud to the king. Soon afterwards the lecturers in London Diocese were curtailed as a prelude to Laud's future work as archbishop. The Directions were reissued in January 1634, and a policy of deliberately reducing certain kinds of lecturer was initiated in several dioceses, pursued in the Metropolitical Visitation, and completed by Laud's supporters amongst the bishops.